2022
DOI: 10.20944/preprints202208.0309.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Positive Mass Balance is the Actual Etiology of Obesity: Time for A Paradigm Shift?

Abstract: According to known laws of physics, chronic positive mass balance is the actual etiology of obesity, not positive energy balance. The relevant physical law in terms of body mass regulation is the Law of Conservation of Mass, not the Law of Conservation of Energy. A recently proposed mass balance model (MBM) describes the temporal evolution of body weight and body composition under a wide variety of feeding experiments, and it seems to provide a highly accurate description of the very best human experimental fe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A growing body of evidence indicate that the widely accepted EBT ("Calories In, Calories Out) is a flawed paradigm. Instead, it is becoming increasingly clear that body mass is regulated according to the "Mass In, Mass Out" principle [2,3,4,5,6,9]. A very comprehensive and detailed review can be found in source [9], while a relatively easy-to-read and practical review can be found in [5].…”
Section: Simulation According To the Mass Balance Model (Mbm)mentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence indicate that the widely accepted EBT ("Calories In, Calories Out) is a flawed paradigm. Instead, it is becoming increasingly clear that body mass is regulated according to the "Mass In, Mass Out" principle [2,3,4,5,6,9]. A very comprehensive and detailed review can be found in source [9], while a relatively easy-to-read and practical review can be found in [5].…”
Section: Simulation According To the Mass Balance Model (Mbm)mentioning
confidence: 99%
“…Instead, it is becoming increasingly clear that body mass is regulated according to the "Mass In, Mass Out" principle [2,3,4,5,6,9]. A very comprehensive and detailed review can be found in source [9], while a relatively easy-to-read and practical review can be found in [5]. Indeed, the results of this well-controlled feeding experiment by Hall et A2.…”
Section: Simulation According To the Mass Balance Model (Mbm)mentioning
confidence: 99%